Clinical Outcomes and Complications of Preoperative Embolization for Intracranial Giant Meningioma Tumorectomy: A Retrospective, Observational, Matched Cohort Study - Yin, Yi; Li, Yuhong; Jiang, Zhouyang; Zhang, Chao; Ge, Hongfei; Chen, Zhi; Hu, Rong; Chen, Yujie; Li, Xuegang; Li, Fei; Feng, Hua (Frontiers in Oncology, 2022)
Objective The potential benefits of preoperative embolization for intracranial meningiomas are still under debate. We aimed to investigate whether preoperative embolization can improve surgical and functional outcomes, based on controlling patient- and tumor-related confounding factors. Methods We reviewed all meningioma cases in our department from January 2016 to May 2021. Cases in the nonembolization cohort were matched to the embolization cohort by 1:1 ratio propensity score matching, through controlling patient- and tumor-related confounds. Surgical outcomes, complications, and functional outcomes were retrospectively compared between these two groups. Results Sixty-six cases in each group were included in our study after being matched. We did not find any significant differences of estimated blood loss (600.00 (400) vs. 500.00 (500.00) ml, p = 0.31), decrease of HGB level (30.81 ± 15.82 vs. 26.59 ± 12.90 g/L, p = 0.09), gross total resection rate (74.24% vs. 77.27%, p = 0.68), surgical time (302.50 (136) vs. 300.00 (72) min, p = 0.48), blood transfusion rates (53.03% vs. 42.42%, p = 0.35), blood transfusion volume [650.00 (657.50) vs. 535.00 (875.00) ml, p = 0.63] between the embolization group and nonembolization group. The number of patients who experience postsurgery complications were significantly higher in the nonembolization group (39.39% vs. 21.21%, p = 0.02). Patients in the nonembolization group were more likely to have a higher rate of mRS decline postsurgery (31.82% vs. 15.15%, p = 0.04). Conclusion Our study showed significant lower rates of surgical complications and long-term disabilities of meningioma patients treated with preoperative embolization. There were no significant differences in estimated blood loss, surgical time, and blood transfusion volume between embolization and nonembolization groups.